DO IDX30 INVESTMENT STOCKS OFFER OPTIMAL RISK–RETURN TRADEOFFS? A POST-COVID STUDY - Kenneth Pinandhito; Nguyen Thi Kim Lien; Dina Yeni Martia; Alvianita Gunawan Putri; Junaedi Adi Prasetyo (Politeknik Negeri Semarang, 2026)
This study aims to analyze the formation of an optimal portfolio of stocks based on the Markowitz model in IDX Quality30 companies post covid from January 2021 to December 2022. The secondary data used are daily closing stock prices. The samples in this study were 19 companies. The analysis results show that ten stocks are optimal portfolio candidates: ASII, BBCA, BMRI, ITMG, KLBF, MIKA, PTBA, SIDO, TLKM, and UNTR. The optimal portfolio formation of the Markowitz model consists of 10 issuers with proportions, namely SIDO 30.81%, TLKM 15.61%, MIKA 12.09%, KLBF 11.90%, BBCA 8.64%, ASII 7.39%, PTBA 5.35%, UNTR 3.73%, ITMG 3.53%, BMRI 0.94%. The proportion of funds generated can provide an expected return value of 0.047% with a risk level (standard deviation) of 0.885%.